PENGARUH LEVERAGE, LIQUIDITY RATIO, FIRM SIZE, ACTIVITY RATIO TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2017-2019 - Wahyudi, Robby; Viriany, Viriany (Jurnal Paradigma Akuntansi, 2024)
The purpose of this study is to obtain empirical evidence regarding the effect of liquidity ratio, leverage, firm size and activity ratio on profit growth in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period. This study uses 15 samples and 45 data from manufacturing sector companies which were selected by purposive sampling method. The data in this study were inputted and calculated using the Microsoft Excel program and processed using the Eviews 12 program. The results of this study indicate that simultaneously liquidity ratio, leverage, firm size and activity ratio have a significant effect on profit growth. While partially the firm's liquidity ratio, firm size and activity ratio have no effect on profit growth. However, the leverage variables have an effect on profit growth.